31 gennaio 2024. È nata la Cyborg Era - Gennari, Mario (Studi sulla Formazione/Open Journal of Education, 2024)
On January 31, 2024, news outlets worldwide reported a successful experiment involving an implant. This led to the creation of a “bionic individual”: a human being with an electronic component integrated into their brain. This component, equipped with artificial intelligence, is designed to enhance natural intelligence by connecting it with computers, databases, and telecommunication systems. The Cyborg Era is born! The article analyzes its genesis and development, considering the multiple causal factors of crisis and crasis that concern the society in which it originates. A reflection on the possibility and promotion of a pedagogical Neohumanism in the Cyborg Era ends on a huge question: what will become of the human being, humanity, and humanism?